Sol phase and sol-gel transition in SnO2 colloidal suspensions - dos Santos, LRB; Craievich, A. F.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Munksgaard Int Publ Ltd, 2000)
The effect of concentration on the structure of SnO2 colloids in aqueous suspension, on their spatial correlation and on the gelation process was studied by small angle x-ray scattering (SAXS). The shape of the experimental SAXS curves varies with suspension concentration. For diluted suspensions ([SnO2] less than or equal to 0.13 mol L-1), SAXS results indicate the presence of colloidal fractal aggregates with an internal correlation length xi congruent to 20 Angstrom, without any noticeable spatial correlation between them. This suggests that the aggregates are spatially arranged without any significant interaction like in ideal gas structures. For higher concentrations ([SnO2] = 0.16, 0.32, and 0.64 mol L-1), the colloidal aggregates are larger (xi = 24 Angstrom) and exhibit a certain degree of spatial correlation between them. The pair correlation function corresponding to the sol with the highest concentration (0.92 mol L-1) reveals a rather strong short range order between aggregates, characteristic of a fluid-like structure, with an average nearest-neighbor distance between aggregates d(1) = 125 Angstrom and an average second-neighbor distance d(2) = 283 Angstrom. The pair distribution function remains essentially invariant during the sol-gel transition, suggesting that gelation involves the formation of a few points of connection between the aggregates resulting in a gel network constituted by essentially linear chains of clusters..